2017
DOI: 10.1097/aog.0000000000001847
|View full text |Cite
|
Sign up to set email alerts
|

Attempted and Successful Vacuum-Assisted Vaginal Delivery by Prepregnancy Body Mass Index

Abstract: Objective To examine rates of attempted and successful vacuum-assisted vaginal delivery by pre-pregnancy body mass index (BMI). Methods We conducted a retrospective cohort study of 2,084 women with singleton gestations needing operative delivery assistance and vacuum-eligible (fully dilated, ≥ +2 station, ≥34 weeks) using 2006–2014 in-patient records. Pre-pregnancy BMI was categorized as underweight (<18.5kg/m2), normal weight (18.5kg/m2≤BMI<25kg/m2), overweight (25kg/m2≤ BMI<30kg/m2), or obese (≥30kg/m2). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A recent prospective cohort study of Norwegian women found 50% higher rates of vacuum-assisted vaginal delivery among women with class III obesity compared to normal weight women [25]. However, a recent study in US showed lower odds of attempted assisted vaginal delivery in obese women, similar to our findings [26]. It should be noted that rates of cesarean delivery in Norway were much lower than those in the US and China during the study period [27].…”
Section: Discussionsupporting
confidence: 86%
“…A recent prospective cohort study of Norwegian women found 50% higher rates of vacuum-assisted vaginal delivery among women with class III obesity compared to normal weight women [25]. However, a recent study in US showed lower odds of attempted assisted vaginal delivery in obese women, similar to our findings [26]. It should be noted that rates of cesarean delivery in Norway were much lower than those in the US and China during the study period [27].…”
Section: Discussionsupporting
confidence: 86%
“…and, to some extent, this is driven by medical staff seeking to minimise risk to the baby and mother. Women who are obese and whose labour is not progressing are less likely than women of ideal weight to be allowed to attempt a vaginal delivery with assistance from forceps or a vacuum cap (ventouse), but, when they are allowed to do so, appear to have better outcomes than ideal weight women 88,89 . With caesarean section recovery is slower and surgical complications are more likely with obesity 90,91 …”
Section: Labour Complicationsmentioning
confidence: 99%
“…Women who are obese and whose labour is not progressing are less likely than women of ideal weight to be allowed to attempt a vaginal delivery with assistance from forceps or a vacuum cap (ventouse), but, when they are allowed to do so, appear to have better outcomes than ideal weight women. 88,89 With caesarean section recovery is slower and surgical complications are more likely with obesity. 90,91 Post-partum haemorrhage occurs in up to 5% of women and is characterised by either heavy blood loss during delivery (in excess of 500 ml following vaginal delivery or 1 litre following a caesarean) or in the following days (as a result of placental retention, uterine atony or rupture).…”
Section: Labour Complicationsmentioning
confidence: 99%
“…This goes along with a recent analysis, that was able to demonstrate an association of vacuum extraction and nulliparity [25]. Ramos et al examined women requiring operative delivery assistance and found a decreased likelihood of vaginal operative delivery in women with pre-pregnancy obesity [26].…”
Section: Discussionmentioning
confidence: 62%